2000
DOI: 10.1145/351440.351445
|View full text |Cite
|
Sign up to set email alerts
|

Teaching computer graphics visual literacy to art and computer science students

Abstract: Although it is a requisite skill for success in industry, visual literacy in graphics is intimidating to computer science and art students. Computer science majors are uneasy about using their eyes to examine images while art students may not have much background in the technical terminology. This column is the second in a two-part series that discusses an interdisciplinary teaching technique that overcomes these obstacles. Part one was published in Computer Graphics 34(1) February 2000… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…In contrast, regarding the digital media samples, the art group scored lower on incredibly few items when compared with the science groups. According to Rödder [61], Eber and Wolfe [62], and Walker et al [63], the reason for this may be that those who possess professional training in art are more adept at processing sensory materials-such as graphics, video and sound-and are more inclined to figurative and pictorial modes of thinking. Regarding the historical photo, the data analysis showed that the art participants found the content difficult to understand and lacking in sensory appeal.…”
Section: Research Findingsmentioning
confidence: 99%
“…In contrast, regarding the digital media samples, the art group scored lower on incredibly few items when compared with the science groups. According to Rödder [61], Eber and Wolfe [62], and Walker et al [63], the reason for this may be that those who possess professional training in art are more adept at processing sensory materials-such as graphics, video and sound-and are more inclined to figurative and pictorial modes of thinking. Regarding the historical photo, the data analysis showed that the art participants found the content difficult to understand and lacking in sensory appeal.…”
Section: Research Findingsmentioning
confidence: 99%
“…Stafford (2011) outlines the use of picture books, film, At third level the teaching of visual literacy has been introduced across the curriculum. For example in: art and design (Andrews, 2016) statistics (Young and Ruediger, 2016), dermatology (Griffin et al, 2016), library and information science (Beaudoin, 2016), inter-disciplinary studies (Little, Felten and Berry, 2015), geography (Hollman, 2014), science, technology, engineering and mathematics (Cook, Teaff and Cook, 2015), politics and international relations (Holland, 2014), teacher training (Wilhelm, 2005) and art and computer science (Eber and Wolfe, 2000).…”
Section: Curricula Integrationmentioning
confidence: 99%
“…RQ1 [31], [21], [29], [12], [6], [9], [5], [32], [25], [19], [20], [10], [3], [35] RQ2 [19], [31], [22], [12], [10], [11], [7], [4], [33], [25], [13], [5], [3], [1], [21], [27], [15], [23], [38], [39], [36], [8], [2], [14]…”
Section: Pregunta Trabajosmentioning
confidence: 99%